(untitled) (Oratio Directa, 2023)
Online media play an important role in informing and educating the public about Indonesia's capital relocation to East Kalimantan. This qualitative study applies Pan and Kosicki's framing analysis to compare Republika.co.id and Tempo.co coverage of the relocation and the inauguration of the capital's zero point. The analysis examines syntactic, script, thematic, and rhetorical structures. The findings show that Republika.co.id tends to emphasize support for government policy, whereas Tempo.co more strongly foregrounds criticism of the government.